Loewen, Teaching What Really Happened: How To Avoid The Tyranny Of Textbooks & Get Students Excited About Doing History - Laing, Annette (Teaching History: A Journal of Methods, 2010)
Since 1995, James W. Loewen’s Lies My Teacher Told Me has enjoyed phenomenal success in both sales and influence. Nobody who has read it can look unskeptically at a history textbook again. Loewen’ s Lies Across America (1999) proved a worthy successor, inviting readers to look critically at the historical plaques and monuments that litter the American landscape. More recently, Loewen turned his attention to the forgotten heritage of structural racism in small-town America, in his 2005 book Sundown Towns. Now, in Teaching What Really Happened, Loewen promises in the subtitle that he will explain How to Avoid the Tyranny of Textbooks and Get Students Excited About Doing History. Loewen has an ambitious goal, and he sets out to fulfill the promise of the subtitle in a volume that appears in the Multicultural Education Series of the Teachers College Press, which suggests another major goal for this book, that of incorporating a more robust multicultural agenda into K-12 history. Neither aim will be surprising to anyone familiar with Loewen’s work, but this time, he attempts to lay out for readers a blueprint of sorts for connecting the two.